Towards Intellectual Property Rights Management Back-office and Front-office Perspectives - Modic, Dolores (Springer International Publishing, 2018)
This book provides insights into the intellectual property rights (IPR) managerial practices of key IPR executives from a range of multinational companies, including major research and development firms. It identifies gaps in IPR management and considers the Tabular Application Development (TAD) methodology IPR process optimisation model. The authors adopt an interdisciplinary approach, providing a conceptual framework derived from practice and enriched with theoretical insights, and offering organisational recommendations. In taking into account both Back and Front office processes, Towards Intellectual Property Rights Management will help businesses navigate the maze of IPR and maximise the value they get from innovation.